Two Conceptual Change Strategies and Junior Secondary School Students’ Learning Outcomes in Basic Science Concepts in Kwara State, Nigeria (2012)
Basic Science is a useful subject for developing scientific knowledge and technological skills in young learners. However, students’ achievement in the subject is dwindling at the junior secondary school level. Numerous efforts made to resolve the problems notwithstanding, little success has been achieved. As part of the sustained efforts in finding new ways of boosting students’ achievement, this study investigated the use of two conceptual change strategies (Simplex and Cognitive Coaching) and the moderating influence of mental ability and self-concept on students’ learning outcomes in Basic Science. The study employed a pretest-posttest, control group, quasi-experimental design, using a 3 x 3 x 2 factorial matrix. Intact classes made up of two hundred and twenty three students, having high, medium and low mental abilities, from six secondary schools in Kwara state were randomly selected. Eight instruments were used for this study: Teacher’s Instructional Guides for: Simplex, Cognitive Coaching and Conventional method; Basic Science Concepts Achievement Test (r = 0.73); Attitude Towards Basic Science Scale (r = 0.83); Mental Ability Test (r = 0.67); Self-Concept Inventory (r = 0.79) and Basic Science Conceptual Change Debriefing Protocol (r = 0.67). Two research questions were answered and seven null hypotheses were tested at the 0.05 level of significance. Data were analysed using Descriptive statistics, Analysis of Covariance (ANCOVA), Scheffe post hoc test and graphs. The two teaching strategies had significant effect on achievement in (F(2,204)=10.624;P < .05), attitude towards (F(2, 204) = 4.360; P < .05) and retention of (F(2,204)=32.602;P<.05) Basic Science concepts. Students exposed to Simplex strategy had the highest post-test mean score ( ̅ = 9.32) on achievement in Basic Science concepts, followed by those of the Cognitive Coaching strategy ( ̅ = 8.85) and the Conventional method ( ̅ = 7.68). The students taught with Conventional method had highest mean score ( ̅ = 53.28) than the Cognitive Coaching strategy ( ̅ = 48.69) and the Simplex strategy ( ̅ = 46.55) on attitude towards Basic Science concepts. For retention of Basic Science concepts, Simplex group had highest mean score ( ̅ = 7.84) than the Cognitive Coaching group ( ̅ = 7.67) and the Control group ( ̅ = 4.91). There was significant effect of mental ability on students’ achievement in (F(2, 204) = 7.600;P<.05) and on their retention of (F(2, 204) = 8.518; P < .05) Basic Science concepts. High mental ability students’ had highest attitude mean score ( ̅ = 51.89) than low mental ability ( ̅ = 48.79) and medium mental ability ( ̅ = 48.16) students’. Self-Concept had significant effect on students’ achievement in Basic Science (F(2, 204) = 4.261; P < .05). Students having low self-concept had higher attitude mean score ( ̅ = 50.20) than those with high self-concept ( ̅ = 49.18). A significant interaction effect existed between teaching strategies and mental ability on students attitude towards Basic Science concepts (F(4, 204) = 2.423; P < .05). The Conventional strategy favoured low and high mental ability students on attitude towards Basic Science concepts than the Cognitive Coaching and Simplex strategies. The medium mental ability students’ had better attitude towards Basic Science concepts with Cognitive Coaching strategy being better than their counterparts in other groups. Simplex and Cognitive Coaching strategies were effective in caausing conceptual change and improving students’ learning outcomes in Basic Science. Basic Science teachers should therefore, use Simplex and Cognitive Coaching strategies for enhancing students’ learning outcomes in Basic Science while also considering the possible additional effects of self-concept and mental ability.